2018
DOI: 10.1136/bmjopen-2018-023708
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a feasibility study of an internet-administered, guided, CBT-based, self-help intervention (ENGAGE) for parents of children previously treated for cancer

Abstract: IntroductionA subgroup of parents of children previously treated for cancer report long-term psychological distress after end of treatment. However, needs for psychological support are commonly unmet and there is a lack of evidence-based treatments tailored to the specific needs of this population. An internet-administered, guided, cognitive–behavioural therapy-based, self-help intervention (ENGAGE) for parents of children previously treated for cancer may provide a solution. The aim is to examine the feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 50 publications
1
42
0
Order By: Relevance
“…Notwithstanding these limitations, this is to our knowledge the first study to examine attitudes toward clinical trials, preferences regarding study design, and willingness to receive internet-administered psychological support among parents of children previously treated for cancer. The results from this study will have considerable implications for the design of a planned feasibility study [47], such as initial study invitations being sent via postal letters by the research team, full study information being presented on Web via both text and video, and the provision of support from a psychologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding these limitations, this is to our knowledge the first study to examine attitudes toward clinical trials, preferences regarding study design, and willingness to receive internet-administered psychological support among parents of children previously treated for cancer. The results from this study will have considerable implications for the design of a planned feasibility study [47], such as initial study invitations being sent via postal letters by the research team, full study information being presented on Web via both text and video, and the provision of support from a psychologist.…”
Section: Discussionmentioning
confidence: 99%
“…Survey findings have further enhanced our understanding of the acceptability of internet-administered approaches for the population, alongside an appreciation of potentially acceptable study procedures and design. Results will inform the design of a feasibility study of an ICBT intervention for parents of children previously treated for cancer [47], to further examine methodological, procedural, and clinical uncertainties [25,50].…”
Section: Discussionmentioning
confidence: 99%
“…The primary feasibility outcome was 60% D100 FC completion among enrolled parents. This threshold was specified a priori 49,50 and is consistent with other feasibility studies among parents of children with cancer, 51 adults with cancer, 52 and adults with dementia, 53 each of which targeted a minimum of 50% to 60% engagement with intervention components. Our target sample size was N = 30 parents, which attains a 2‐sided exact binomial 95% CI width of 37% when the observed feasibility proportion is 60% (95% CI, 41%‐77%).…”
Section: Methodsmentioning
confidence: 99%
“…Secondary ( process ) feasibility outcomes included 70% enrollment and training of eligible fellows and NPs ( frontline oncology providers) based on an estimated eligible pool of 14 (attaining a 95% CI width of 50%). The primary acceptability outcome was a threshold of 70% of parents who “agree/strongly agree” that “D100 was helpful,” as measured by the follow‐up survey 51 . Assuming that 18 of 30 parents completed the D100 FC, the 95% CI width is 45% for an observed agreement proportion of 70% (95% CI%, 44‐89%).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, an Australian study has shown promising results in terms of feasibility and acceptability for an online group-based psychological intervention for parents of survivors of childhood cancer [25]. We have furthermore developed an internet-administered guided, CBT-based selfhelp intervention for parents whose children have ended successful treatment, which is currently tested in terms of feasibility [26,27]. Should the intervention be demonstrated to be clinically and cost-effective (or at least cost-neutral), the same intervention development process will be used for the development of an intervention for bereaved parents.…”
Section: Psychologistsmentioning
confidence: 99%